2016
DOI: 10.1103/physrevb.94.235208
|View full text |Cite
|
Sign up to set email alerts
|

Realistic inversion of diffraction data for an amorphous solid: The case of amorphous silicon

Abstract: We apply a new method "force enhanced atomic refinement" (FEAR) to create a computer model of amorphous silicon (a-Si), based upon the highly precise X-ray diffraction experiments of Laaziri et al. [14]. The logic underlying our calculation is to estimate the structure of a real sample a-Si using experimental data and chemical information included in a non-biased way, starting from random coordinates. The model is in close agreement with experiment and also sits at a suitable minimum energy according to densi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…Recently, Drabold et al introduced a new "information-driven" paradigm, wherein the knowledge of both experimental constraints and the interatomic forcefield is simultaneously leveraged to produce realistic atomic models of glasses [26]. Specially, Drabold et al proposed a force-enhanced atomic refinement (FEAR) method, which relies on an iterative combination of RMC refinements (i.e., based on available experimental constraints) and energy minimizations (i.e., based on the knowledge of the interatomic forcefield) [7,26,27]. Unlike alternative hybrid RMC approaches-wherein both structure and energy are optimized simultaneously-the interatomic forces are here only computed during the energy minimization steps, which results in an improved overall computational efficiency [26].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Drabold et al introduced a new "information-driven" paradigm, wherein the knowledge of both experimental constraints and the interatomic forcefield is simultaneously leveraged to produce realistic atomic models of glasses [26]. Specially, Drabold et al proposed a force-enhanced atomic refinement (FEAR) method, which relies on an iterative combination of RMC refinements (i.e., based on available experimental constraints) and energy minimizations (i.e., based on the knowledge of the interatomic forcefield) [7,26,27]. Unlike alternative hybrid RMC approaches-wherein both structure and energy are optimized simultaneously-the interatomic forces are here only computed during the energy minimization steps, which results in an improved overall computational efficiency [26].…”
Section: Introductionmentioning
confidence: 99%
“…chemical calculations can also be extremely valuable in their own right, as they intrinsically incorporate accurate information about the higher order interactions in materials. These calculations remain very computationally intensive for the large system sizes needed to accurately describe amorphous materials, although recent work has shown that an approach combining RMC refinement with ab initio relaxation can overcome the configurational barriers to reorganisation that have limited the application of quantum chemical calculations thus far, resulting in much more realistic models of amorphous materials 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…In the case of WWW and BM models, all the atoms in the generated samples are four-fold coordinated. This percentage is reduced to 88 − 90% in conventional RMC models [25,40], while it was increased to 96 − 99% in improved RMC models [26][27][28]. The percentage of fourfold-coordinated atoms is unrealistic for some RMC models [28,41] and the paracrystalline models analyzed [43].…”
Section: Resultsmentioning
confidence: 95%
“…The inherent variability of the a-Si configuration and properties depending on the fabrication process make the proper modeling of its structure difficult. An adequate understanding of the amorphous structure is needed, and recent studies demonstrate the interest in providing realistic atomistic models of amorphous solids that reproduce the structure of experimental samples [25][26][27][28][29]. a-Si has been considered as a prototype for tetrahedrally coordinated covalent amorphous materials, which can be described as a continuous random network (CRN) [6,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation